PENGARUH PENGALAMAN KERJA, KOMPETENSI DAN MOTIVASI KERJA TERHADAP KINERJA APARATUR SIPIL NEGruh Pengalaman Kerja, Kompetensi dan Motivasi Kerja terhadap Kinerja Aparatur Sipil Negara pada Kantor Kecamatan Maritengngae Kabupaten Sidenreng Rappang - nur'eni.A eni; Mashur Razak; Sudirman Dandu (Jurnal Aplikasi Manajemen & Kewirausahaan MASSARO, 2022)
This study aims to determine and analyze (1) the effect of work experience, competence and work motivation partially and simultaneously on the performance of the State Civil Apparatus at the Maritengngae Subdistrict Office, Sidenreng Rappang Regency (2) the most dominant variable affecting the performance of the State Civil Apparatus at the Subdistrict Office. Maritengngae, Sidenreng Rappang Regency. Data collection methods used are questionnaires and document studies. The analytical method used is descriptive statistical analysis and multiple linear regression analysis. The results showed that (1) partially work experience, competence, and motivation had a positive and significant effect on the performance of the State Civil Apparatus at the Maritengngae District Office, Sidenreng Rappang Regency (2) simultaneously work experience, competence and work motivation had a positive and significant effect on performance. employees of Maritengngae District, Sidenreng Rappang Regency. This means that the better the work experience, competence and work motivation possessed by the employee, the better the employee's performance will be (3) the competency variable has the most dominant and significant influence on employee performance in the Maritengngae sub-district, Sidenreng Rappang Regency.